2019
DOI: 10.1128/mbio.02596-18
|View full text |Cite
|
Sign up to set email alerts
|

Capacity To Utilize Raffinose Dictates Pneumococcal Disease Phenotype

Abstract: S. pneumoniae is a component of the commensal nasopharyngeal microflora of humans, but from this reservoir, it can progress to localized or invasive disease with a frequency that translates into massive global morbidity and mortality. However, the factors that govern the switch from commensal to pathogen, as well as those that determine disease tropism, are poorly understood. Here we show that capacity to utilize raffinose can determine the nature of the disease caused by a given pneumococcal strain. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 36 publications
2
43
1
Order By: Relevance
“…However, the decline in this tri-saccharide during colonization of P. expansum may indicate the ability of this pathogen to degrade raffinose in order to utilize it as carbon source (Fang and St Leger, 2010). This ability to degrade raffinose may be significant to its virulence, as was previously shown for bacterial pathogens (Minhas et al, 2019). These results are in line with the transcriptomic analysis, which indicated that P. expansum has a significantly higher carbon metabolism than C. gloeosporioides.…”
Section: Effects Of Colletotrichum and Penicillium Colonization On Hosupporting
confidence: 86%
“…However, the decline in this tri-saccharide during colonization of P. expansum may indicate the ability of this pathogen to degrade raffinose in order to utilize it as carbon source (Fang and St Leger, 2010). This ability to degrade raffinose may be significant to its virulence, as was previously shown for bacterial pathogens (Minhas et al, 2019). These results are in line with the transcriptomic analysis, which indicated that P. expansum has a significantly higher carbon metabolism than C. gloeosporioides.…”
Section: Effects Of Colletotrichum and Penicillium Colonization On Hosupporting
confidence: 86%
“…6B). Interestingly, Spn ear isolates demonstrate a reduced capacity to use the sugar raffinose comparing with blood isolates 61 .…”
Section: Spn Growth Stimulation Is Hemoglobin-dependent and Utilizes mentioning
confidence: 99%
“…In contrast to iCJ415, iDS372 cannot grow on either stachyose or raffinose, which is due to lack of a raffinose degrading reaction (Stachyose is degraded to raffinose). Raffinose utilization by S. pneumoniae has been shown to be an independent predictor for disease spectrum (Minhas et al, 2019).…”
Section: Experimental Verification Of Carbonand Nitrogen Utilization mentioning
confidence: 99%